Development of cyberweapons using Artificial Intelligence (2019)
This book presents both the investigative and practical advances along with their respective results of the directed work Development of cyberweapons using Artificial Intelligence. The book has the investigative and functional development of different tools based on the use of natural language processing for the detection of cyber terrorism and analysis of intelligence information, in order to prevent and contain future terrorist activities and outline adversaries.